StormPav Green Pavement as Parking Lot and Stormwater Detention Pond for Flash Flood Mitigation at Taman Uni Garden Kota Samarahan, Sarawak - Lukman, Mohd Najib; Norazlina, Bateni; Darrien Mah, Yau Seng (Semarak Ilmu Publishing, 2025)
Flood disturbances have an impact on the economy and society. Previous research has focused on the causes of floods resulting in urbanization, poor drainage networks, maintenance, and climate change. This study aims to develop an integrated stormwater management solution in the Kota Samarahan district's floodplain area in Sarawak, Malaysia. This paper aims to evaluate the causes of the flood and the potential of detention storage, namely StormPav as a sub-surface detention pond storage permeable parking lot to mitigate flood in the study area. The study area has experienced floods almost every year since 2015, during the Northeast Monsoon season in the middle of December and early January. The main outlet received about 2286 m3 of overflow water when projected with 10 Average Recurrence Interval (ARI) rainfall, causing a flash flood to the commercial building next to the main outlet area. The field study is conducted to evaluate the existing hydraulic drainage network. The existing drainage network of the catchment area is modelled in Stormwater Management Model (SWMM) version 5.1. Next, the scenario with a flood is simulated in SWMM. Finally, flood mitigation using StormPav is assessed using Low Impact Development (LID) control in SWMM. The results show that StormPav reduced peak flow runoff by about 32.55% and 31.15% for 10 ARI and 100 ARI, respectively, with subsurface detention storage.